Helping teens work through grief - Perschy, Mary Kelly, 1942- (Brunner-Routledge, 2004)
This book is a valuable guide, helping adults connect with grieving teens. The reader will find background information along with many specific activities to help teens reflect upon and talk about their particular concerns.